FRI0527 Efficacy of bio-optimised curcuma extract (FLEXOFYTOL®) for painful knee osteoarthritis: data from copra, a multicenter randomised controlled study. (12th June 2018) - Henrotin, Y.; Malaise, M.; Wittoek, R.; Devlam, K.; Brasseur, J.-P.; Luyten, F.; Jiangang, Q.; Van den Berghe, M.; Uhoda, R.; Bentin, J.; De Vroey, T.; Erpicum, L.; et al.
Abstract : Background: Flexofytol is a Curcuma Longa extract with an increased bioavailibility (bio-optimised) by mixing curcuma extract with polysorbate. Objectives: To demonstrate the effects of Flexofytol on OA symptoms and soluble biomarkers. Methods: 141 patients with symptomatic knee OA (mean age 61.8 years [min.45-max.86]; 80.1% female; mean K and L grade of the knee 2.4; mean BMI 29.7 kg/m 2 ) were randomised in a prospective double blinded, 3 parallel groups, comparative and multicenter, study (NCT02909621 ). At inclusion, all patients took pain killers or anti-inflammatory drugs which were authorised during the study. Patients received 6 months continuous treatment with either high dose Flexofytol (n=49, 140.01 mg Curcuma longa L. extract/treatment), low dose Flexofytol (n=47, 93.34 mg Curcuma longa L. extract/treatment) or placebo (n=45, Sunflower seed oil fill ingredient). Each treatment corresponded to 3 oral capsules two times a day to respect the blinding. All patients had clinical assessment (knee pain, knee function and patient global assessment of disease activity [PGADA]) and blood sampling for biomarkers measurements (usCRP and sColl2–1) at baseline (T0), 1 month (T1), 3 months (T3) and 6 months (T6). Additionally, patient compliance, satisfaction and tolerance were assessed at each timepoint following baseline. Primary outcome was the change at 3 months versus baseline in type II collagen degradation -specific biomarker sColl2–1 and VAS PGADA. Results: Comparison of time evolution curves showed that sColl2–1 levels were lower in the treated groups but differences were not significant. The decrease in PGADA overtime was significantly more important in low dose group than in placebo group only at the 1 month evaluation timepoint (low dose ▵T1-T0, −12, 5 mm vs placebo ▵T1-T0, −2 mm, p=0.035). Further, the knee pain relief was significantly higher in low dose group at T1 and T3 than in placebo (low dose ▵T1-T0, −16.5 mm vs placebo ▵T1-T0, −4 mm p=0.046; low dose ▵T3-T0, −36.5 mm vs placebo ▵T3-T0, −8 mm p=0.043). No difference was observed at T6. No differences were seen for any parameter when the high dose group was compared with the placebo group at any time point. The global KOOS score and its subscales significantly decreased overtime but changes were comparable in each group. Additionally, patient compliance was good and patient satisfaction remained stable overtime in each group. The ratio of patients with adverse events (AE) related to the product were similar in placebo and treated groups but the number of AE linked to the product was higher in the high dose group than in placebo (p=0.012). Conclusions: Flexofytol, at a low dose, induced a rapid symptomatic relief on knee pain and a beneficial effect on the patient assessment of disease. This study also provides information on the dose to use and the design of a larger phase III clinical trial. Disclosure of Interest: Y. Henrotin Consultant for: Tilman SA, M. Malaise: None declared, R. Wittoek: None declared, K. Devlam: None declared, J.-P. Brasseur: None declared, F. Luyten: None declared, Q. Jiangang: None declared, M. Van den Berghe : None declared, R. Uhoda: None declared, J. Bentin: None declared, T. De Vroey: None declared, L. Erpicum: None declared, Y. Dierckxsens Employee of: Tilman SA